2015
DOI: 10.2146/ajhp150474
|View full text |Cite
|
Sign up to set email alerts
|

Hospital delirium treatment: Continuation of antipsychotic therapy from the intensive care unit to discharge

Abstract: The continuation of antipsychotics for the management of delirium during transitions of care was a common practice at a tertiary care medical center. Patients receiving antipsychotics for treatment of delirium in the MICU were inappropriately continued on these agents when transferred from the MICU to the medical floor or discharged from the hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
68
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 24 publications
1
68
1
Order By: Relevance
“…In a retrospective review of 59 medical ICU patients who were started on an antipsychotic during an ICU stay for delirium, 33% were discharged from the hospital on the antipsychotic without an indication for continuing the medication . In another study, geriatricians, hospitalists, and pharmacists were surveyed and reported that as many as 80% of discharge prescriptions for antipsychotic medications were inappropriate …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In a retrospective review of 59 medical ICU patients who were started on an antipsychotic during an ICU stay for delirium, 33% were discharged from the hospital on the antipsychotic without an indication for continuing the medication . In another study, geriatricians, hospitalists, and pharmacists were surveyed and reported that as many as 80% of discharge prescriptions for antipsychotic medications were inappropriate …”
mentioning
confidence: 99%
“…Although long-term antipsychotic treatment is not recommended for treatment of delirium-associated behavioral changes, many studies demonstrate a significant number of patients started on antipsychotics, for this reason, are given high doses of antipsychotics or continued on antipsychotics after hospital discharge. [10][11][12][13][14][15] Patients with ongoing behavioral symptoms of delirium that interfere with treatment or safety may benefit from continued antipsychotic treatment at discharge; however, there is a growing concern for inappropriate continuation at the same time. In a retrospective review of 59 medical ICU patients who were started on an antipsychotic during an ICU stay for From the Duke University Health System, Durham, North Carolina.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of 100 patients, 23 received prescriptions for amiodarone upon discharge without a cardiology consult or referral . Failure to deprescribe medications intended for short‐term inpatient use was also reported in previous studies concerning antipsychotic prescription for elderly patients admitted to the ICU for delirium and therapy was continued upon discharge, despite resolution of delirium …”
mentioning
confidence: 62%
“…12 Failure to deprescribe medications intended for shortterm inpatient use was also reported in previous studies concerning antipsychotic prescription for elderly patients admitted to the ICU for delirium and therapy was continued upon discharge, despite resolution of delirium. 13,14 A recent Dutch study revealed that a large proportion of older adults in the Netherlands had a high load of anticholinergic/sedative medications associated with inappropriate use carrying the risk of both adverse effects including falls and hospitalization as well as increased health costs. 15 The authors of that study declared that prospective strategies are needed to optimize the use of these medications in elderly patients aided by a deprescribing approach, especially considering that few interventions are available but effective in reducing a patient's anticholinergic/sedative load.…”
mentioning
confidence: 99%